The - Dainty, Peter (Oxford University Press, 2000)
All he wanted to do was to marry the woman he loved. But his country said 'No!' He was Edward VIII, King of Great Britain, King of India, King of Australia, and King of thirty-nine other countries. And he loved the wrong woman. She was beautiful and she loved him - but she was already married to another man. It was a love story that shook the world. The King had to choose: to be King, or to have love ...and leave his country, never to return